Develop an internal audit methodology for evaluating environmental policies and procedures (An Applied Study in the General Company for Food Industries / Al Ameen Vegetable Oils Factory) - Sohad Sabih Alsaffar; Noor Sabah Hussain (Journal of Madenat Alelem University College, 2021)
Abstract The problem of environmental pollution emerged with the advent of the Industrial Revolution, affecting human and ecosystems. It has extended to the human, health, psychological and social fields. Internal audit of the environment is one of the important sources of compliance with environmental laws, regulations, and programs. The research aims to: 1. Clarify the concept of internal audit of the environment. 2. Proposing a model that can be adopted in evaluation of environmental performance through policies and procedures. The research is based on the hypothesis that the research in the presentation and presentation of its concepts is based on the hypothesis that the internal audit of the environment is an integral part of financial and performance auditing within the framework of the comprehensive audit, which requires development and raise the level of professional performance. The research has reached a set of conclusions that can be summarized as follows: (1) There are weaknesses in measures to reduce environmental impacts. (2) There is little interest in providing people with environmental expertise and appropriate rehabilitation. (3) The Unit is not interested in informing external parties of new environmental measures. (4) There are preparations in the unit to prevent or inform potential incidents that have an impact on the environment, but these are not updated periodically.